Non-specific chronic low back pain in patients with scoliosis—an overview of the literature on patients undergoing brace treatment - Weiss, Hans-Rudolf (J Phys Ther Sci, 2019)
[Purpose] Although there is evidence that non-specific chronic pain can be influenced by physical therapy, some patients with scoliosis and chronic pain may benefit from additional brace treatment. The purpose of this review is to answer the question whether there are studies on the use of brace treatment in patients with scoliosis and pain and to investigate whether brace treatment does positively influence chronic pain. [Methods] A PubMed review has been undertaken using the key words (1) scoliosis and pain and brace treatment and (2) scoliosis and pain and orthotics. From both searches the studies were extracted that included a patient group with the diagnosis of a scoliosis and with additional chronic non-specific low back pain, treated with a brace. [Results] One hundred forty two items have been found for search (1) and 111 for search (2). The total number of relevant items found in both searches was 10. According to the studies found, bracing seems an effective treatment for this condition. [Conclusion] Brace treatment in patients with scoliosis and chronic non-specific low back pain has demonstrated to be effective. It should be used when exercise treatment is not effective. A clinical test is demonstrated to predict the most beneficial approach in brace treatment.